Impact of Egg Exposure to UV Filter-Spiked Sediment on the Survival, Hatching Success, Cardiac Frequency, and Metabolic Scope of Zebrafish Embryos - Julie Lucas; Valentin Logeux; Alice M. S. Rodrigues; Didier Stien; Philippe Lebaron (Oceans, 2022)
Chemical UV filters are increasingly used in cosmetics to protect skin from UV radiation. As a consequence, they are released into the aquatic environment via recreational activities and wastewaters. In aquatic ecosystems, fish eggs in contact with sediment can be affected by organic and lipophilic pollutants such as UV filters. The present study aims to evaluate the toxicity of six individual UV filters, diethylhexyl butamido triazone (DBT), diethylamino hydroxybenzoyl hexyl benzoate (DHHB), ethylhexyl triazone (ET), 2-ethylhexyl salicylate (ES), homosalate (HS), and octocrylene (OC), in the embryo-larval stages of zebrafish Danio rerio. Contamination of fish eggs and larvae with UV filters occurred through contact with spiked sediment for 96 h at a concentration of 10 μg g−1. Among the six UV filters tested, OC delayed hatching success, whereas ES significantly increased the heartbeat rate of embryo–larvae after sediment exposure, probably as a stress response.